SARS Cov‐2 infection in a renal‐transplanted patient: A case report. Issue 7 (10th May 2020) - Seminari, Elena; Colaneri, Marta; Sambo, Margherita; Gallazzi, Ilaria; Di Matteo, Angela; Roda, Silvia; Bruno, Raffaele; ,
Abstract : The clinical manifestation of COVID‐19 can vary from an asymptomatic course to ARDS requiring invasive mechanical ventilation and extracorporeal membrane oxygenation. A kidney transplanted patient infected with SARS CoV‐2 infection showed a mild disease despite immune suppression. It is possible that Immunosuppression can "be protective" as the cytokine storm is an important factor in the disease story. Despite the good outcome reported in the present case report, is remains of vital importance the solid organ transplant patients use precautions in order to avoid the infection. Abstract : A kidney‐transplanted patient infected with SARS‐CoV‐2 shows a mild disease despite immune suppression, leading the authors to think it may be possible that immunosuppression can be protective, as the cytokine storm is an important factor in the disease story.